Pengaruh Variabel Moneter dan Utang Luar Negeri terhadap Inflasi di Indonesia - Hadmawati, Nidya; war, Muna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research has purpose to determine the effect of variables of money supply, BI rate, and external debt on inflation in Indonesia. The data used are quarterly data for the period 2005.3-2014.3. With analysis tools Error Correction Model (ECM) using EViews 7.0. The results showed that both long-term and short-term variables of money supply, BI rate, external debt, exchange rate IDR/USD, and import overall can influence on inflation in Indonesia from 2005.3-2014.3. In partial BI rate, exchange rate IDR/USD, and import significant positive influence on inflation in Indonesia in the long term and short term. For the variables of money supply and external debt cannot influence on inflation in the long term. While in the short term, in partial variable of money supply significant negative influence on inflation in Indonesia. Â Keywords: Inflation, Money Supply, BI Rate, External Debt, Error Correction Model (ECM)